A descriptive study of the clinico-pathological and surgical characteristics of patients with primary epithelial ovarian cancer. A cross sectional study - Sindiani, Amer (Ann Med Surg (Lond), 2020)
OBJECTIVE: To study the clinical, pathological and surgical features of primary epithelial ovarian cancer treated at our institution. METHODS: fifty-nine patients with primary epithelial ovarian cancer were included. Clinical data collected included patient's age, presenting symptoms, laboratory and tumor markers results as well as preoperative imaging reports. Pathological and surgical findings included were: spread of the disease, histologic type, stage of the disease, type of surgical procedure and amount of residual disease. RESULTS: Mean age of the patients was 54.5 years. Lower abdominal pain was the most common presenting symptom, followed by abdominal distension. The commonest histopathological type was high grade serous carcinoma (72.9%). In our study, majority of patients were diagnosed with stage III disease, accounting for 69.5% of the total number of patients. Complete cytoreduction with no gross residual disease was achieved in 77.3% of patients with stage 3–4 disease. CONCLUSION: clinical and pathological features of primary epithelial ovarian carcinoma in our populations are similar to what is reported worldwide. We have also documented that our surgical approach to the management of ovarian cancer is comparable to the international consensus.